Treating Heart Inflammation With Interleukin-1 Blockade in a Case of Erdheim–Chester Disease - Tomelleri, Alessandro; Cavalli, Giulio; De Luca, Giacomo; Campochiaro, Corrado; D’Aliberti, Teresa; Tresoldi, Moreno; Dagna, Lorenzo (Frontiers in Immunology, 2018)
Pericarditis is an inflammatory heart disease, which may be idiopathic or secondary to autoimmune or auto-inflammatory diseases and often leads to severe or life-threatening complications. Colchicine and non-steroidal anti-inflammatory drugs represent the mainstay of treatment, whereas use of corticosteroids is associated with recurrence of disease flares. While effective and safe anti-inflammatory therapies remain an unmet clinical need, emerging clinical and experimental evidence points at a promising role of inhibition of the pro-inflammatory cytokine interleukin-1 (IL-1). We thus evaluated treatment with the IL-1 receptor antagonist anakinra in a case of extremely severe pericarditis with cardiac tamponade and heart failure secondary to Erdheim–Chester disease (ECD), a rare clonal disorder of macrophages characterized by rampant inflammation and multiorgan involvement. A 62-year-old man was admitted to the Emergency Department with severe pericardial effusion requiring the creation of a pleuro-pericardial window. A whole-body contrast-enhanced computed tomography pointed at a diagnosis of ECD with involvement of the heart and pericardium and of the retroperitoneal space. Over the following days, an echocardiography revealed a closure of the pleuro-pericardial window and a relapse of the pericardial effusion. Treatment with anakinra, the recombinant form of the naturally occurring IL-1 receptor antagonist, was started at a standard subcutaneous dose of 100 mg/day. After 2 days, we observed a dramatic clinical improvement, an abrupt reduction of the inflammatory markers, and a reabsorption of the pericardial effusion. Anakinra was maintained as monotherapy, and the patient remained asymptomatic in the absence of disease flares for the following year. Recent studies point at inhibition of IL-1 activity as an attractive treatment option for patients with refractory idiopathic recurrent pericarditis. Anakinra treatment may also have a role in patients with pericarditis in the setting of systemic inflammatory disorders, such as ECD.